The CRM project management handbook building realistic expectations and managing risk - Gentle, Michael 1957- (Gale virtual reference library, 2002)
Stresses a back-to-basics approach that favors tactical rather than strategic customer relationship management (CRM). Identifies the common stumbling blocks that threaten all CRM projects and proposes practical solutions to get around them. Identifies critical success factors and risk factors, and features a range of case studies (both successes and failures) and a 40-question risk analysis.